Detection of active compounds in Aloe vera leaf extract and their inhibitory effect on Pseudomonas aeruginosa. - Fadhil, Khansaa; Saeed, Ibrahim Omar; Saleh, Mahmood Khalaf (Technium BioChemMed, 2024)
In the study, two types of Aloe vera leaf extracts were prepared: aqueous and alcoholic extract. The research was conducted at the Department of Life Sciences, Faculty of Science, Tikrit University. From October to January. The active compounds in these alcoholic extracts were detected as tannins, cladosides, saponins, and flavonoids, all of which gave a positive result. The antibacterial activity of the aqueous and alcoholic extracts were estimated at concentrations ranging from (200-12. 5) mg/ml, where the alcoholic extract gave a high efficacy of (34.5) mm, while the aqueous extract had a lower efficacy (29.6) mm at the same concentration. Microbial tests were evaluated using different combinations of the extracts on Pseudomonas aeruginosa isolates, where the alcoholic extract gave the highest inhibitory efficacy to the bacteria.